Development of an integrated failure mode effect and criticality analysis (FMECA) and analytical hierachy process (AHP) for automotive stamping part - Mohd Razikin, Mohd Azroy (2015)
In competitive business world, organizations must be able to respond to changing market needs quickly, efficiently and responsively. Therefore, the shortcomings of the conventional approach that can contribute to inefficiency, time-consuming and not being able to provide the required performance should be improved in order to respond to the current situation. Thus, the main objective of this research is to propose a new integration of the Failure Mode Effect and Criticality Analysis (FMECA) and the Analytical Hierarchy Process (AHP) so that can be used in the automotive stamping part (known as tie plate) manufacturing industry. A case study was performed in order to reduce the number of processes, time, and labour by implementing the proposed integration approach. FMECA was used to identify the failure in tie plate stamping process and four design concepts of packaging jig were proposed to eliminate and reduce the failure. AHP was used to determine the best design concept of the packaging jig as variety of aspects have to be considered in the selection such as performance, maintenance, development time, development cost, safety and potential cause of failure. Design concept 3 was selected as the best design concept with the highest score of 31.9%. The research shows that the proposed integration approach was used to generate and select the best design concept of packaging jig while the jig had reduced the number of stamping processes by 33.3% (from 6 to 4 processes), time by 50% (from 20 to 10 minutes for packaging per box) and labour by 50% (from 4 to 2 persons). This research presents the importance of considering the integrated approach in the design stage in order to improve the manufacturing process activities, especially in the automotive stamping parts industry.